THE CHARACTER OF ICHABOD CRANE AS A REFLECTION OF HUMAN GREED AND FOOLISHNESS IN WASHINGTON IRVING’S THE LEGEND OF SLEEPY HOLLOW - Shancelldeep Kaur; Ira Febri Yanti Simanjuntak; Nurhayati Purba (Jurnal Cakrawala Ilmiah, 2026)
literary characters often function as reflections of human nature and moral values. This study analyzes the character of Ichabod Crane in Washington Irving’s The Legend of Sleepy Hollow as a representation of human greed and foolishness. Using a qualitative descriptive method, this research examines Ichabod Crane’s actions, motivations, and psychological traits through characterization theory and moral-psychological approaches. The findings reveal that Ichabod Crane’s intellectual ability is overshadowed by material ambition and irrational fear, leading to his moral and social downfall. This study concludes that Irving employs Ichabod Crane as a moral critique of human weakness, emphasizing that intelligence without moral wisdom results in failure. The research contributes to literary studies by highlighting the relevance of moral criticism in classic American literature.